2012
DOI: 10.1021/bc300324c
|View full text |Cite
|
Sign up to set email alerts
|

Polyaminoquinoline Iron Chelators for Vectorization of Antiproliferative Agents: Design, Synthesis, and Validation

Abstract: Iron chelation in tumoral cells has been reported as potentially useful during antitumoral treatment. Our aim was to develop new polyaminoquinoline iron chelators targeting tumoral cells. For this purpose, we designed, synthesized, and evaluated the biological activity of a new generation of iron chelators, which we named Quilamines, based on an 8-hydroxyquinoline (8-HQ) scaffold linked to linear polyamine vectors. These were designed to target tumor cells expressing an overactive polyamine transport system (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…As reported above, such a concept has been proposed to target other molecules. Our in vivo data, with a low level of side effects, reinforce those obtained in vitro showing the higher sensitivity of proliferating HCT116 cells compared to confluent cells, as well as those previously reported, showing that cells not expressing the PTS are less sensitive to HQ1-44 [29]. In addition, the HQ1-44 targeting can be reinforced through polyamine metabolism manipulation using polyamine depletion tools by providing animals with a polyamine-deficient diet and DFMO, an inhibitor of polyamine biosynthesis, in their drinking water.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As reported above, such a concept has been proposed to target other molecules. Our in vivo data, with a low level of side effects, reinforce those obtained in vitro showing the higher sensitivity of proliferating HCT116 cells compared to confluent cells, as well as those previously reported, showing that cells not expressing the PTS are less sensitive to HQ1-44 [29]. In addition, the HQ1-44 targeting can be reinforced through polyamine metabolism manipulation using polyamine depletion tools by providing animals with a polyamine-deficient diet and DFMO, an inhibitor of polyamine biosynthesis, in their drinking water.…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that the Quilamine HQ1-44 was highly taken up by the PTS and displayed an efficient antiproliferative activity [29]. As expected during the design of Quilamines, the polyamine chain, involved in the metal coordination, reinforced the affinity for iron (III) and the ferric complex was shown to adopt preferentially a 1:2 [Fe/HQ1-44] stoichiometry at pH = 7.4.…”
Section: Polyamine a Vector For Anticancer Agentsmentioning
confidence: 68%
See 2 more Smart Citations
“…Then the diamine was treated with t-butyloxy carbonyl ((Boc) 2 O) to give the monoprotected amine 13 in 71% yield. Exposure of compound 13 to vinyl nitrile 5 resulted in an aza-Michael addition reaction to afford amine 14 in 98% yield, 14 and then the remained amino group of 14 was subjected to benzyl chloroformate to furnish compound 15 in 90% yield, which underwent hydro- Letter Syn lett genation in the presence of Raney Ni and hydrogen (3 MPa) to deliver the corresponding amine 6 in 88% yield. 15 Treatment of compound 6 with freshly prepared acyl chloride 3 followed by deprotection of the Boc group gave amine 16 in 84% yield for two steps.…”
Section: Letter Syn Lettmentioning
confidence: 99%